1997
DOI: 10.1111/j.1399-3089.1997.tb00166.x
|View full text |Cite
|
Sign up to set email alerts
|

The acceptability of pig organ xenografts to patients awaiting a transplant

Abstract: As the waiting lists for allotransplants of heart, kidney, and liver continue to grow, alternative sources of organs for transplantation are being sought: xenografts from pigs to humans could be a solution. However, is this solution acceptable to patients? To answer this question, we sought opinions, using a questionnaire, from 277 patients on a waiting list for a cadaver transplant for either a kidney (207), heart, or heart/lung transplant (70); there was a 65% (188) response rate. Approximately 75% of respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 7 publications
2
16
0
Order By: Relevance
“…Arundell et al. indicated that the frequency of acceptance was not higher among those patients who had waited for a long time than among those who had waited for a short time [11]. This is also in line with the results of Schlitt et al.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Arundell et al. indicated that the frequency of acceptance was not higher among those patients who had waited for a long time than among those who had waited for a short time [11]. This is also in line with the results of Schlitt et al.…”
Section: Discussionsupporting
confidence: 73%
“…According to the authors, there were no significant differences in the responses of the three patient groups. Arundell and McKenzie reported that patients with chronic peritoneal dialysis (n=38) were slightly less interested (42 vs. 55%) in a xenograft than those on hemodialysis (n=75) [11].…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 What is your attitude toward receiving a kidney from an animal with the same result and risk of infection as with transplantation from a human? The operation can be planned and performed within 3 Missing answers 1 3 P < 0.001 (Mann-Whitney), P-value for test of difference in attitude…”
Section: Attitud S Towmi! Kidney Trans Lants From Mimalsmentioning
confidence: 99%
“…Results of surveys conducted in Canada [16], France [17] and the USA [18] suggest a positive attitude to xenotransplantation: about half the general public would consider a xenograft if a human organ or tissue were unavailable. Transplant recipients [19] and patients waiting for transplantation [20,21] are the most in favor of xenotransplantation. A survey of Swedish university students’ views on the use of animals in biomedical research and xenotransplantation showed that three of four respondents accepted xenotransplantation [22].…”
Section: Introductionmentioning
confidence: 99%